PERKEMBANGAN DAN PEMIKIRAN UANG DARI MASA KE MASA - Sari, Sepri Wulan (IAIN Tulungagung, 2016)
Money is seen not only as a legal tender (legal tender) but is also seen as a commodity that has its price through interest rates, then the nature of money has increasingly shifted away from the truth. Historically the money was divided into three categories, namely cash items, paper money, credit money or demand deposits. While initially people do not know the money, but do exchange between barter goods and services. This type of research used in this discussion is the use of Library Research while the use of the techniques used is content analysis or study the contents. The emergence of money as a solution to facilitate the transaction. In addition, money is also already known in many nations, among others Nations Lydia, the Greeks, the Romans, the Persians, the reign of Islam. In addition to already implemented by some of the nation but has a different concept, but it is also a lot of scholars who give the concept of money as Al-Ghazali, Al-Maqrizy and Ibn Khaldun.Keywords: Development, Thought, Money